Purification and characterization of selenocysteine beta-lyase from Citrobacter freundii. - Chocat, P (1985)
The purification and characterization of bacterial selenocysteine beta-lyase, an enzyme which specifically catalyzes the cleavage of L-selenocysteine to L-alanine and Se0, are presented. The enzyme, purified to near homogeneity from Citrobacter freundii, is monomeric with a molecular weight of ca. 64,000 and contains 1 mol of pyridoxal 5'-phosphate as a cofactor per mol of enzyme. L-Selenocysteine is the sole substrate (Km, 0.95 mM). L-Cysteine is a competitive inhibitor of the enzyme (Ki, 0.65 mM). The enzyme also catalyzes the alpha, beta elimination of beta-chloro-L-alanine to form NH3, pyruvate, and Cl- and is irreversibly inactivated during the reaction. The physicochemical properties, e.g., amino acid composition and subunit structure, of the bacterial enzyme are fairly different from those of the pig liver enzyme (Esaki et al., J. Biol. Chem. 257:4386-4391, 1982). However, the catalytic properties of both enzymes, e.g., substrate specificity and inactivation by the substrate or a mechanism-based inactivator, beta-chloro-L-alanine, are very similar.